The Refusal Speech Act Techniques Employed by Native Sorani Kurds and American English Speakers - Broosk Ali Jalil (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The following is a comparative study between Kurdish Sorani Dialect and American English in terms of the strategies both speakers rely on to give refusals during different daily life situations. This study uses discourse completion task (DCT) method to collect the data. The different circumstances are consisted of four which include invitations, requests, offers and suggestions initiated by lower, higher and equal status persons to receive refusals by the participants. The participants are from different educational backgrounds being B.A., M.A. Degrees holders, schoolteachers, accountants and administrators in different parts of Sorani speaking areas of Iraqi Kurdistan. The strategies used in giving refusals by the participants will be compared to those used by the American native speakers of English given in Abed (2011) which is based on the direct and indirect refusal strategies benchmarked by Beebe et al. (1990:55-73) to find out whether Kurdish speakers of Sorani dialect use different ways to give refusals in such situations during communication. The differences are quite remarkable especially when it comes to the sensitivity towards the interlocutor. It was found that the Sorani Kurds swear to God and they are more sensitive towards both lower and higher status speakers and more sensitive in general than the native speakers of American English.